Correlates of Adoption of Groundnut Cultivation Technology: A Micro Level Study from Odisha (Indian Journal of Extension Education, 2020)
Being a cash crop, groundnut plays a vital role in Indian economy with its total production increased by two folds during 1950-51 to 2018-19. The present study was carried out in Dhenkanal and Angul districts of Odisha with an aim to assess the socio-economic characteristics of the groundnut farmers which may have potential impact on the adoption pattern of the recommended technology. Both purposive and random sampling procedure was adopted in selection of 220 respondents. Data were collected through pre-tested structured interview schedule. Majority (78.63%) of the farmers were found in medium level of adoption category followed by low level (15.91%) and high level (5.46%) of adoption. Variables viz., social participation, extension participation, exposure to mass media, attitude, and knowledge had significant positive association with the level of adoption of the technology. Age was found to be negatively correlated with the level of adoption of groundnut cultivation technology. It is suggested that blanket recommendation of technology has to be substituted with customized technology package suiting to the socio-economic profile of the farming community.